13C Photoassimilate partitioning in sweet cherry (Prunus avium) during early spring - Ayala,Marlene (Pontificia Universidad Católica de Chile. Facultad de Agronomía e Ingeniería Forestal, 2015)
Stored reserves are critical for the early spring growth of reproductive and vegetative sinks in sweet cherry (Prunus avium L.). To study the distribution of carbon storage reserves on new, highly productive hybrid rootstocks in sweet cherry, an experiment was established using 5-yr-old cv. 'Regina' on the semi-vigorous rootstock 'Gisela®6' ('GI®6'). Using whole-canopy enclosure chambers, five trees were pulse-labeled three times with high levels of 13CO2 during the fall. At leaf drop, leaves, buds, wood, bark and roots were sampled for gas chromatography-mass spectrometry (GC-MS) analysis. The storage organs with the highest percentages of excess 13C atoms were the roots and the older wood in the trunks, branches and buds. During the spring, newly developing organs (flowers, immature fruits and leaves) were sampled weekly from bloom to stage III of fruit development for additional GC-MS analysis. 13C-reserves were remobilized and partitioned to flowers, fruits and young leaves from before budbreak (side green stage) until 14 days after full bloom (DAFB). The isotopic composition differed significantly between phenological stages, and the highest 13C levels in the growing sinks were detected between bloom and fruit set. The reproductive organs had the strongest sink activity until 14 DAFB, and competition with spur leaf sink activity was apparent. It is proposed that reserve source limitation may impact fruit set and spur leaf development, which may ultimately impact the availability of photoassimilate during the later stages of fruit growth.